2023
DOI: 10.1007/s10570-023-05164-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of lignocellulose nanofibrils by conventional and microwave-assisted deep-eutectic-solvent pretreatments: mechanical, antioxidant, and UV-blocking properties

Abstract: Herein for the rst time, lignocellulose nano brils (LCNF) were prepared from pine-wood powder using microwave (MW)-assisted deep eutectic solvent (DES) pretreatment coupled with high-pressure homogenization. A DES based on choline chloride and lactic acid was employed, and LCNFs prepared by conventional DES pretreatment at 110°C (LCNF-110) and 130°C (LCNF-130) were used for comparison.Although MW treatment offered a high removal of lignin (70%) and hemicellulose (90%) within a short time (110 s), the morpholog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…7b). 68 From these examples, it can be concluded that when the particle size of lignin is reduced, especially to the nanoscale, it can exhibit better compatibility with the matrix of the membrane material. This can result in uniform dispersion, ultimately leading to a lightening of the membrane's color.…”
Section: Traditional Issues and The Resolving Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…7b). 68 From these examples, it can be concluded that when the particle size of lignin is reduced, especially to the nanoscale, it can exhibit better compatibility with the matrix of the membrane material. This can result in uniform dispersion, ultimately leading to a lightening of the membrane's color.…”
Section: Traditional Issues and The Resolving Solutionsmentioning
confidence: 99%
“…One is directly made of the LCNF (lignocellulosic nanofibril) containing lignin and cellulose naturally, and the other is the composite material that combines the separated lignin and cellulose artificially. 68–72…”
Section: Biodegradable Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, lignin-containing cellulose nanofibrils (LCNFs) have garnered significant interest as a new class of nanosized lignocellulosic material that could expand the domains of application of nanocelluloses. The presence of lignin in LCNFs likely imparts specific properties, including ultraviolet (UV)-absorption, antioxidant activity, hydrophobicity, barrier properties, and emulsification improvement in Pickering emulsions, among others. , Numerous studies have demonstrated the beneficial effects of the presence of residual lignin on the reduction of hydrophilicity, water uptake, and water permeability of nanopapers, particularly when the lignin content exceeded 15 wt %. , For example, thin films of high-lignin content CNFs (23 wt %) were reported to be suitable for producing low oxygen permeability films with an oxygen transmission rate (OTR) comparable to commercially available polymers like poly­(ethylene terephthalate) (PET) . Other applications encompass the use of LCNFs as an emulsifying agent for oil-in-water (O/W) Pickering emulsions, being an attractive alternative to synthetic surfactants .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of lignin in LCNFs likely imparts specific properties, including ultraviolet (UV)-absorption, antioxidant activity, hydrophobicity, barrier properties, and emulsification improvement in Pickering emulsions, among others. 1 , 2 Numerous studies have demonstrated the beneficial effects of the presence of residual lignin on the reduction of hydrophilicity, water uptake, and water permeability of nanopapers, particularly when the lignin content exceeded 15 wt %. 3 , 4 For example, thin films of high-lignin content CNFs (23 wt %) were reported to be suitable for producing low oxygen permeability films with an oxygen transmission rate (OTR) comparable to commercially available polymers like poly(ethylene terephthalate) (PET).…”
Section: Introductionmentioning
confidence: 99%